The Use Of Technology Improves The Sales Value Of Farmers - Khairuman Man Man; Hery Setiawan (Jurnal Inotera, 2018)
Aceh province based on BPS data 2017 has 1.2 million inhabitants have a livelihood as a farmer. Of this amount includes the number of farmers in each of the regency in Aceh. One of district that has a population of farmers that is the South Aceh Regency with a large producer of young plants (palawija), horticulture and plantation crops Ruak Village is one of the villages in North Kluet Subdistrict with farmers in the form of coffee, corn, lime and rice. The villagers of Ruak have a livelihood as farmers, both farmers and farmers as well as daily laborers in the local farmers' business. Farmers in the village of Ruak are abundant every year. Based on the data that was successfully obtained during the survey that the farmers in the village of Ruak produced an average yield of 150 tons per year. Every year the village of Ruak lags behind to contribute to the community with the results of farmers produced by the farmers of the of Ruak village. The contribution of the farmers of the village of Ruak is not proportional to the celebrations obtained. This causes very high production costs, starting from the cost of plants, buying medicines, fertilizers, tools and daily payment instruments. The cost to plant to harvest is very high. Sometimes not comparable with the selling price of farmers. Prices are not in line with European expectations. Because the market price that has been determined by the parties cannot be negotiated by the farmers and because of the market price.